Effect of Hydrophobic Excipients on the Release Behavior of Dexamethasone and Betamethasone from Biodegradable Poly (DL-lactide) Polymeric Implants - Khan, Fariba; Mahmud, Tasnuva; Islam, M Saiful; Jalil, Reza-ul (Bangladesh Journal of Scientific and Industrial Research, 2010)
This study was conducted with the aim of formulating injectable in-situ forming implants of biodegradable poly (D,L-poly lactic acid) (DLPLA) with steroidal drugs. Two steroidal drugs betamethasone sodium phosphate and dexamethasone sodium phosphate were selected as model drug. Different hydrophobic excipients such as sorbitan esters of lauric acid (Span 20), sorbitan esters of oleic acid (Span 80), cetyl alcohol, glyceryl monostearate, glyceryl dibehenate (CompritolAT088®), glyceryl palmito-stearic ester (Precirol®) were used. In-vitro dissolution of 7 days was performed to investigate the effect of these excipients on the release of betamethasone and dexamethasone from insitu forming DL-PLA implants. Drug release data were fitted in different models to characterize release mechanism. Both betamethasone and dexamethasone release were found to follow Korsmeyer model. Glyceryl palmitostearate was found to reduce the release of both betamethasone and dexamethasone most. Time for 25% release (t25), 50% release (t50), and 75% release (t75) of the drugs were calculated. Mean dissolution time (MDT) values were also calculated from the dissolution data. MDT (day) was 2.48±0.2 and 2.31±0.3 for betamethasone and dexamethasone respectively for implants containing no excipient. Incorporation of all the excipients (except span 20) increased these MDT values for both of the drugs indicating sustained release nature of the excipients. Key words: In-situ implants; Poly (D,L-lactic acid); Betamethasone; Dexamethasone; Hydrophobic excipients; Sustained release DOI: 10.3329/bjsir.v45i3.6527 Bangladesh J. Sci. Ind. Res. 45(3), 189-196, 2010